Integration of cellulases recycling with 2nd generation bioethanol production from waste paper residues - Gomes, Daniel Gonçalves (2015)
Nowadays, the economic feasibility of 2G-bioethanol depends on two important factors: raw material and the cost of enzymes. Using urban and industrial residues may represent a significant improvement, as it refers to a material with a negative cost and with no soil competition. One of these materials is the recycled paper sludge (RPS), which presents a considerable fraction of carbohydrates, but is currently disposed on landfills. Also, the high cost of cellulases demands immediate improvements on their efficiency, where enzyme recycling comes as a promising strategy to achieve that. Here we study the potential of RPS on 2G-bioethanol coupled with a strategy of cellulase recycling. Firstly, after determining a glucan content of only 16 % on RPS, some studies were conducted to increase this fraction. With the neutralization of the carbonates present on RPS, it was possible to considerably increase glucans content to 30 %. Using this new material and employing a high dosage of celluclast, an 86 % saccharification efficiency was obtained within 48 hours at a temperature of 30ºC. Measurements of enzymatic activity in the different fractions indicated a high degree of total activity conservation during the hydrolysis process. Also, it was observed that 84 % of the initial total activity remained on the liquid fraction after hydrolysis, confirming the high potential for enzyme recycling. Current efforts aim the improvement of hydrolysis kinetics using higher temperatures, close to the optimum conditions for cellulases action. However, considering the negative effects of these conditions, a higher thermostability system is required, which will be pursued in the following studies.